QUALITY MALAYSIAN ENGLISH LANGUAGE TEACHERS: EXAMINING A POLICY STRATEGY - Napisah Kepol (UUM Press, 2019)
Purpose â€" The purpose of this paper is to examine and discuss one of the strategies in the latest Malaysian language education policy Memartabatkan Bahasa Malaysia Memperkukuh Bahasa Inggeris (MBMMBI) (To Uphold Bahasa Malaysia and to Strengthen the English Language). The strategy in focus is aimed at improving the quality of English language teachers. This strategy is examined in light of selected research findings and other information that is deemed relevant to a beneficial discussion of the topic. Methodology â€" The method employed was document analysis which involved intensive reading of the Malaysian Ministry of Education information booklets about the MBMMBI policy and other related documents and resources providing supplementary information about the policy. Findings â€" The analysis showed that of the five sub-strategies proposed in the main strategy targeted at improving the quality of English language teachers, three of them addressed the commonly included aspects of knowledge, skills and abilities found in the definitions of teacher quality in the literature. Teacher disposition and evaluation, another two aspects often related to teacher quality, were not included.   Conclusion â€" Quality was not featured consistently in the policy strategy analysed. Overall, the policy did not capture the full complexity of the concept of teacher quality. Whether the omission of the other attributes of teacher quality has had any effect on the  aspirations of the policy remained to be seen. Follow-up strategies were suggested such as monitoring, evaluation, reinforcement, and support strategies to ensure that the policy in practice would have the desired impact as envisaged by the policy makers.   Significance â€" The quality of teachers has frequently been linked to student achievement in schools. This association between teacher quality and student achievement provides reason for an examination and discussion of the topic of research conducted in this paper. It is also hoped that this paper will provide some impetus for further discussions of English language teacher quality in the current Malaysian educational context.